Reviving Focused Scrutiny in the Constitutional Review of Public Health Measures - Robert Gatter (Washington University Journal of Law & Policy, 2021)
State and local officials have issued public health orders aiming to prevent or slow the spread of COVID-19. As a result, constitutional challenges have been brought claiming that certain measures (stay-at-home orders, mask mandates, etc.) violate the right to free exercise of religion, the right to free assembly, and the right to due process. This Article acknowledges the highly deferential standard applied when assessing whether a government’s public health action, during a public health emergency, violates the due process clause. Gatter encourages judges to adopt “focused scrutiny” in these cases, further constraining judicial review by a scientific focus. This review can be applied to any standard. Courts applying focused scrutiny focus their attention to the known science of the infectious disease as well as evidence of the efficacy of the government’s public heath measure. When both the government’s public health action and the constitutional review of the action occur during a declared emergency, Gatter argues this method is necessary to off-set the risk of judicial rubber stamping, defend against public health policy driven by fear or politics, and to strengthen the scientific basis of public health measures taken during the pandemic.
Keywords: COVID; COVID-19; coronavirus; coronavirus pandemic; pandemic; constitutional; constitution; constitutional rights; rights; public health; public health orders; orders; government order; scrutiny; focused scrutiny; emergency; emergency order